2022
DOI: 10.1371/journal.pdig.0000003
|View full text |Cite
|
Sign up to set email alerts
|

Best practices in the real-world data life cycle

Abstract: With increasing digitization of healthcare, real-world data (RWD) are available in greater quantity and scope than ever before. Since the 2016 United States 21st Century Cures Act, innovations in the RWD life cycle have taken tremendous strides forward, largely driven by demand for regulatory-grade real-world evidence from the biopharmaceutical sector. However, use cases for RWD continue to grow in number, moving beyond drug development, to population health and direct clinical applications pertinent to payors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 65 publications
0
34
0
1
Order By: Relevance
“…It also opens the door towards analyses of ‘similar patients’ for purposes of virtual trials of multimorbidity. The advent of reliable and scalable NLP methods integrated within the healthcare data lifecycle 31 brings much more expressive clinical data into a research-ready state and enables all downstream data-dependent activity including population health, business intelligence, and epidemiological and clinical research on real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…It also opens the door towards analyses of ‘similar patients’ for purposes of virtual trials of multimorbidity. The advent of reliable and scalable NLP methods integrated within the healthcare data lifecycle 31 brings much more expressive clinical data into a research-ready state and enables all downstream data-dependent activity including population health, business intelligence, and epidemiological and clinical research on real-world data.…”
Section: Discussionmentioning
confidence: 99%
“…A healthcare data lifecycle describes generation, curation and aggregation, and maintenance of patient data that is used by consumers (such as clinicians and researchers) and patients themselves 37 . Practical examples can be seen in Learning Healthcare Systems, where analysis is built into daily practice 38 .…”
Section: Outside Of the Algorithmmentioning
confidence: 99%
“…As previously noted, it is without doubt encouraging that, recently, HTA bodies have started recognising that health inequalities should no longer be ignored in decision-making for new technologies; in the UK, NICE encouraged further research on how health inequalities can be quantitatively accounted for (as another type of decision-modifier) in the clinical and cost-effectiveness assessment of new technologies. Moreover, RWE collection need also to prioritise diversity to reduce bias and maintain equity in patient representation; for example, previous studies have shown that increase in data from medical wearables only increase the gap between those with and without access to interconnected devices ( Zhang et al, 2022 ; Scientific Reports, 2022 ). It is also encouraging that, FDA has just drafted detailed guidance to improve clinical trial diversity by explicitly requesting manufacturers to demonstrate that measures have been taken to enhance diversity in clinical trials ( FDA, 2022 ).…”
Section: Introductionmentioning
confidence: 99%